(untitled) (Revista de Física Médica, 2018)
3D image guided brachytherapy, based exclusively on MR has been introduced into clinical practice for the treatment of patients undergoing gynecological brachytherapy for cervical cancer. Recently, this brachytherapy modality shows a significant progress since the appearance of new type of applicators incorporating interstitial components with the aim of better coverage of volumes outlined on MR images. This report gathers the work of the Brachytherapy Group of the Spanish Society of Medical Physics (SEFM), dedicated to gynecological brachytherapy of cervical cancer based exclusively on MR. The goal of this report is to combine practical aspects, summary of literature and recommendations of scientific societies in order to ease other members of the SEFM with the implementation of this technique. This report summarizes many aspects involved in the whole process of the MR brachytherapy. Firstly, a description of the commercially available applicators is done, focusing on those having interstitial component. Secondly, some considerations about the use of MR imaging are described. A summary of recommendations published by relevant organisations or societies are also detailed in the document. Finally, and based on the experience of the members of this task group, many considerations and proposals are discussed about different aspects involved in the planning process, reconstruction alternatives, optimization methods, prescription and reporting. The use of ultrasonography is also included in this report due to its good prospects and increasing role in these procedures. The report ends with a description of specific aspects about commissioning and considerations about uncertainty analysis in this MR image based modality of brachytherapy of cervical cancer.